Social action in times of crises in the MENA region: Sociocultural community development as a lever of social change - Garcia Delahaye, Sylvia; Saleh, Samah; Dormeier Freire, Alexandre (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2021)
As a tribute to the thinking of Jean-Claude Gillet, this article aims to make accessible in the English language some of the notions of sociocultural community development and its function developed by this author in relation to their testing during a recent training course on the theme of Social action in times of crises: sociocultural community development as a lever of social change in the Middle East and North Africa region. Based on the knowledge of the participants and faculty members, this paper proposes a broad reflection on sociocultural community development as it is currently experienced and desired in various countries (Yemen, Syria, Libya, Iraq, Lebanon, Jordan and Palestine). This reflection, co-constructed from contexts experienced by the participants and selected contributions in reference to inspiring authors such as Gillet, seems necessary today for the potential development of intervention and investigation tools supporting social change in the English-speaking Arab countries.